2011
DOI: 10.1158/0008-5472.can-11-0821
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma-Derived Epidermal Growth Factor Receptor Carboxyl-Terminal Deletion Mutants Are Transforming and Are Sensitive to EGFR-Directed Therapies

Abstract: Genomic alterations of the epidermal growth factor receptor (EGFR) gene play a crucial role in pathogenesis of glioblastoma multiforme (GBM). By systematic analysis of GBM genomic data, we have identified and characterized a novel exon 27 deletion mutation occurring within the EGFR carboxyl-terminus domain (CTD) in addition to identifying additional examples of previously reported deletion mutations in this region. We show that the GBM-derived EGFR CTD deletion mutants are able to induce cellular transformatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 44 publications
(47 reference statements)
6
66
0
Order By: Relevance
“…These genomic events include somatic EGFR mutations within regions of either the extracellular domain, in glioblastoma, or the kinase domain in lung adenocarcinoma,3, 4 as well as through gene amplification as observed in many other types of solid tumors 5, 6. In addition, several intragenic deletions within either the extracellular or C‐terminal domain of EGFR have also been reported to be oncogenic in a subset of glioblastoma and lung adenocarcinoma 7, 8, 9…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These genomic events include somatic EGFR mutations within regions of either the extracellular domain, in glioblastoma, or the kinase domain in lung adenocarcinoma,3, 4 as well as through gene amplification as observed in many other types of solid tumors 5, 6. In addition, several intragenic deletions within either the extracellular or C‐terminal domain of EGFR have also been reported to be oncogenic in a subset of glioblastoma and lung adenocarcinoma 7, 8, 9…”
mentioning
confidence: 99%
“…Furthermore, accumulating data suggest that the downstream signaling pathways activated by oncogenic mutant EGFR differ from those activated by ligand stimulated wild‐type EGFR 17, 18, 19. Notably, C‐terminal deletion EGFR mutants, lacking some or all of the autophosphorylation sites that have been identified in GBM and lung adenocarcinoma, are able to induce cellular transformation 8, 9, 20. These observations have raised the question whether autophosphorylation of oncogenic mutant EGFR, which is a consequence of constitutive receptor dimerization, is required for oncogenic activation and induction of cellular transformation by cancer‐derived EGFR mutants.…”
mentioning
confidence: 99%
“…An analysis of 469 GBM samples from the TCGA data for the presence of Cterminal exonic deletions confirmed the presence of three different C-terminal deletions of EGFR: exons 25-28 (EGFRvV), exons 25-27 (EGFRvIV), and exon 27 (Cho et al 2011). Forced expression of each EGFR-CTD mutant in Ba/F3 cells promoted IL3 independent growth, demonstrating oncogenic function and EGF ligand-independent receptor autophosphorylation.…”
Section: Alternative Splicing Of Egfrmentioning
confidence: 87%
“…Forced expression of each EGFR-CTD mutant in Ba/F3 cells promoted IL3 independent growth, demonstrating oncogenic function and EGF ligand-independent receptor autophosphorylation. Importantly, expression of EGFR-CTD mutants in LN443 GBM cells significantly increased their tumorigenicity in an intracranial mouse model compared to control (Cho et al 2011).…”
Section: Alternative Splicing Of Egfrmentioning
confidence: 94%
“…Our experiments suggest that this mutation is not associated with the response to an HER4 ligand. Several studies have shown that other HER family gene mutations occurring within the C-terminal domain, such as EGFR C-terminal deletion mutations, have oncogenic activity and transformational ability and that they are effectively inhibited by EGFR-targeted drugs (39,40). These findings suggest that constitutive asymmetric dimerization may be one of the possible mechanisms of oncogenic activation (39,40).…”
Section: Discussionmentioning
confidence: 99%